2007
DOI: 10.1145/1186810.1186813
|View full text |Cite
|
Sign up to set email alerts
|

Frugal path mechanisms

Abstract: We consider the problem of selecting a low-cost s - t path in a graph where the edge costs are a secret, known only to the various economic agents who own them. To solve this problem, Nisan and Ronen applied the celebrated Vickrey-Clarke-Groves (VCG) mechanism, which pays a premium to induce the edges so as to reveal their costs truthfully. We observe that this premium can be unacceptably high. There are simple instances where the mechanism pays Θ( n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
156
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(156 citation statements)
references
References 19 publications
0
156
0
Order By: Relevance
“…The study of frugality in the context of mechanism design was initiated by Archer and Tardos [20]. They investigated the frugality of path auctions in weighted directed graphs and showed that the total payment of any truthful mechanism for path auctions can be a linear factor of the second optimal disjoint path.…”
Section: B Frugalitymentioning
confidence: 99%
“…The study of frugality in the context of mechanism design was initiated by Archer and Tardos [20]. They investigated the frugality of path auctions in weighted directed graphs and showed that the total payment of any truthful mechanism for path auctions can be a linear factor of the second optimal disjoint path.…”
Section: B Frugalitymentioning
confidence: 99%
“…The high overpayment issue in VCG-based LCP routing was first noticed by Archer and Tardos [2]. They investigated the frugal path problem (FPP), which aims at designing a mechanism that selects a path and induces truthful cost revelation, but without paying high price.…”
Section: Related Workmentioning
confidence: 99%
“…They investigated the frugal path problem (FPP), which aims at designing a mechanism that selects a path and induces truthful cost revelation, but without paying high price. The work in [2] primarily contributed negative results for the FPP by showing that no reasonable mechanism can always avoid paying a high premium to induce truthtelling.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The first path is cheapest with true cost 0, but every edge in it receives a VCG incentive payment of 1 (the cost difference between the two paths), so the total VCG cost is the path length. In [AT02,AT07] it is shown that any truthful mechanism has bad worst-case s-t path overpayment. Additional investigations of shortest paths in a worst-case setting appear in [MPS03,ESS04,CR04,Elk05].…”
Section: Introductionmentioning
confidence: 99%